Analisis Pengaruh Kompensasi, Pelatihan Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Motivasi Pegawai Sebagai Variabel Intervening Pada Kementerian Investasi/Bkpm Tahun 2023 - Alamsah; Edi Sugiono (ITB AAS Indonesia Surakarta, 2025)
Abstract This research is a quantitative study with a descriptive approach, namely an approach that makes a number of previous studies the main topic to build and prove the hypothesis in this article. The data used in this article is primary data that researchers obtained from various credible sources, namely 150 Indonesian students and 150 Malaysian students who use credit cards and m-banking. The existing data was collected and then analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the hypothesis used in this article can be accepted and proven. The hypothesis in question is all hypotheses where the first hypothesis is that the Islamic Financial Literacy Of Indonesian Students variable can have a positive relationship direction and a significant influence on Customer Decisions. This is because the P-Values ​​value is positive and is below the significance level of 0.05, namely 0.001. This is because good Islamic Financial Literacy can make researchers access how to register and use Islamic Bank m-banking, think about doing something easier, and enjoy things that work effectively. In line with the reasons in the first hypothesis, the second hypothesis shows similar and more significant results than the first hypothesis, namely the P-Values ​​value is at 0.000. Through these two results, it can be concluded that Islamic Financial Literacy in Indonesia is better than Islamic Financial Literacy in Malaysia. Keywords: Islamic Financial Literacy, Indonesian, Malaysian, Student